Longitudinal development of young talented speed skaters: Physiological and anthropometric aspects - de Koning, J. J.; Bakker, F. C.; de Groot, G.; van Ingen Schenau, G. J. (Journal of Applied Physiology, 1994)
Dutch National Junior Speed Skating Team members (N = 24) were monitored from age 16-17 yr to 20-21 yr. A number of anthropometric and physiological variables changed. There were no differences between successful and unsuccessful speed skaters on the anthropometric variables. At the younger age, successful and unsuccessful skaters were similar on oxygen consumption, mechanical efficiency, and power output. Later, successful skaters were distinguished from unsuccessful one by their having higher power output values. Implication. There were no anthropometric or physiological variables on which speed-skating performance at age 20-21 yr could be predicted from measurements taken at a junior age.